Przesłanki wizyty prezydenta Stanów Zjednoczonych Richarda Nixona w Moskwie w dniach 22-30 maja 1972 roku - Porczyńska, Anna (Acta Universitatis Lodziensis. Folia Historica, 2005)
The Policy of Peaceful Competition realized by President of the United Stales Richard Nixon on the turn of 1960s and 1970s resulted in the peaceful dialogue between the United States of America and the Union of Soviet Socialist Republics concerning disarmament. The circumstances of the summit talks in Moscow were: the inclination to consolidation of international security and peace propagated by the Eastern European Socialdemocratics in the conception of disengagement and conception of the peaceful coexistence of slates which have different social systems restored during the 20th and 22nd Congress of Communist Party of the USSR. Agreements about the fragmentary limitations of nuclear armaments were the proof of these conceptions on the turn of 1960s and 1970s. The other circumstances were: fiasco of the American policy in Wietnam and tense relations between Moscow and Peking, which were permitted The Nixon Administration to take the advantage of that rapprochement with the People’s Republic of China to establish a dialogue with the USSR. The encouragement to bcgining a dialogue was A Peaceful Programme, which Brezniev announced of the turn of March and April 1972 concerning a new foreign policy of the USSR to detente between East and West. The fundamental circumstance of the summit talks in Moscow was the acknowledgement by the United States and the USSR, at the end of 1960s, that nuclear parity exsisted, which was linked with continual expenses for armaments and new technology of armaments by both powers. Moreover, the leaders of the USSR wanted to sign the economic agreement with the United States which would allow to avoid disastrous economic situation in the USSR. One should add the efficient control of the realization of the agreements accepted by the states in the field of disarmament which was possible due to using the national technical control measures. All these circumstances resulted in the visit of the President of the United Stales in Moscow in May 1972 and it initiated signing the agreements of limitation of strategic armaments, scientific, technical and cultural cooperation between both superpowers.